TINJAUAN YURIDIS PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA MASA LALU MELALUI REKONSILIASI - Rian Adelima Sibarani; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a legal state that is obliged to give awards and guarantee protection against human rights issues. Various human rights violations since the old order still have not got legal certainty, gross human rights violations also almost always involve the state apparatus, either actively or passively. The victims experienced various acts of violence: physical, mental, until the loss of life. Whereas, the most responsible party to protect and maintain the fulfillment of human rights every individual or citizen is the state through the state apparatus / tool.To prosecute gross human rights violations established by the Human Rights Court within the General Courts. To implement it, Law Number 26 Year 2000 on Human Rights Court was established. Article 4 states that the Human Rights Court has the duty and authority to examine and decide cases of gross human rights violations.The difficulty of working through the formal legal process to deal with past human rights crimes, as mentioned above, is a strong impetus for the need for alternative settlement mechanisms, commonly known as the